Development of Integrated Learning Pattern by Using Household Learning Activities for Health Promotion: A Case Study of Students at Nakhon Ratchasima Rajabhat University - สัตยวงศ์ทิพย์ พุฒิพงศ์; สละวงษ์ลักษณ์ ทองทิพย์ (Ratchaphruek Journal, 2018)
ABSTRACT The objective of the research was to develop the integrated learning pattern of the demography subject by using household learning activities for health promotion and model evaluation. The research was divided into 3 stages; 1) to study the context 2) to create and improve the learning pattern and 3) to study the result of the improved pattern usage. The samples were 90 students in the Faculty of Public Health, Nakhon Ratchasima Rajabhat University. The household learning activities for health improvement were the mechanism driving the project. The project was one group experiment taking 10 weeks (2 hours per week). The research tools were the learning assessment congruent to the subject standard and learning achievement test of demography subject. The descriptive statistic was used and presented by mean, S.D., and paired t-test; which the difference is found of 95% confidence interval (95%CI). The results were as the following; 1. The integrated learning pattern of demography subject, which was congruent to the subject standard developed, was comprised of 5 elements;1) Stimulus, 2) Presentation, 3) Individual inquiry, 4) Constructivism, and 5) Evaluation. 2. After the experiment the students had more significantly higher learning assessment scores than before the experiment (p<0.05). It indicated that the improved integrated - learning pattern was effective which should be used in the learning management.